TCF-1 maintains CD8+ T cell stemness in tumor microenvironment. Issue 3 (28th May 2021) - Wen, Shuqiong; Lu, Huanzi; Wang, Dikan; Guo, Junyi; Dai, Wenxiao; Wang, Zhi
Abstract: T cell factor 1 (TCF-1) is a transcription factor (TF) of the canonical Wnt signaling pathway that encoded by the Tcf7 . The crucial role of TCF-1 in T cell development and memory formation has been widely recognized. Recent studies have demonstrated that exhausted CD8 + T cell with the expression of TCF-1 may have inspiring function to amplify immunoreaction and improve the response to immunotherapy in chronic viral infection and cancer. In this short review, we summarized recent progress in intratumoral exhausted CD8 + T cells expressing TCF-1 that represent a fantastic subset with stem cell-like properties that associated with improved antitumor immunity and response to immune checkpoint blockade (ICB). Graphical Abstract: Summarizes recent studies showing that intratumoral exhausted CD8 + T cell-expressed TCF-1 is a unique subset; possesses stem cell-like properties that improve both antitumor immunity and the response to immune-checkpoint blockade.